Disrupting the Gatekeepers: Artificial Intelligence-Based Fatwas and the Reconfiguration of Religious Authority in Islamic Educational Management - Aziz Alhajj, Irfan Qowwiyul; Asha , Lukman; Apriani , Eka; Warlizasusi , Jumira; Kurniawan (Corolla International Conference, 2025)
Artificial Intelligence (AI) has begun to penetrate religious spheres, including in the form of digital fatwas. The presence of AI as a generator of instant religious answers challenges the traditional roles of scholars (ulama) and educators within the Islamic education system. This study aims to explore the perceptions of Islamic education actors regarding this phenomenon, analyze its epistemological and managerial impacts, and formulate strategies that educational institutions can adopt in responding to this disruption. The research utilizes an exploratory qualitative approach with a multi-case study across three Islamic educational institutions with distinct characteristics. The results indicate a shift in authority, tensions between traditional scholarly heritage and modern technology, and the emergence of a hybrid authority model. The conceptual contribution of this study is the proposal of a scholarly authority management model based on human-AI collaboration, termed hybrid authority.